2001
DOI: 10.1108/10650740110397060
|View full text |Cite
|
Sign up to set email alerts
|

Solving reusability problems of online learning materials

Abstract: Observes that the widespread use of the World Wide Web for educational purposes creates many opportunities for reusing learning material. However, many factors are involved that may decrease the amount of actual reuse that occurs. Presents a theoretical model of these factors, one of which is the physical layout of learning objects. Approaches this problem by separating the layout of learning objects from their content. This is achieved by describing the content in the eXtensible Markup Language (XML) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 3 publications
0
11
0
2
Order By: Relevance
“…The genericity of a learning object is affected by the number of references it contains to the context in which it is used (Hiddink, 2001). It has been suggested that to make learning materials generic the designer should avoid using references to local institutions, companies, people, courses, topics, etc.…”
Section: Genericity and Contextualitymentioning
confidence: 99%
See 3 more Smart Citations
“…The genericity of a learning object is affected by the number of references it contains to the context in which it is used (Hiddink, 2001). It has been suggested that to make learning materials generic the designer should avoid using references to local institutions, companies, people, courses, topics, etc.…”
Section: Genericity and Contextualitymentioning
confidence: 99%
“…It has been suggested that to make learning materials generic the designer should avoid using references to local institutions, companies, people, courses, topics, etc. (Hiddink, 2001). …”
Section: Genericity and Contextualitymentioning
confidence: 99%
See 2 more Smart Citations
“…The numerical value of the matrix elements gives the number of paths between two nodes in Figure 2. For instance, t 15 …”
Section: A Gozinto-type Modelmentioning
confidence: 99%